2008 Triennial Surveillance Review : Overview Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This triennial surveillance review (TSR) takes place in a time of change, with the Fund in the midst of a major refocusing effort. That surveillance has not been as effective as it should be has been amply documented, notably in previous surveillance reviews and several IEO evaluations. Since the 2004 review of bilateral surveillance (BSR), considerable efforts have been made to enhance its effectiveness, including an overhaul of the policy framework with the adoption of a new Surveillance Decision in 2007. And as part of the refocusing effort, more change is underway to deliver on the Managing Director's vision of an institution making better use of its comparative advantage, to be 'more alert to emerging issues, more critical in its assessments (especially in good times), and more assertive in communicating its concerns.'.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet